A 10-year follow-up service evaluation of the treatment pathway outcomes for patients in nine in-patient psychiatric rehabilitation services. (February 2023) - Edwards, Tom; Meaden, Alan; Commander, Martin
Abstract : Aims and method: This study examines the treatment pathway outcomes over a 10-year period for patients in nine rehabilitation wards at the beginning of this time period. Results: Data were obtained on 85 patients, of whom 59 were discharged during the 10-year period; 29 were readmitted, of whom 15 had further in-patient rehabilitation admissions. Nineteen patients remained in hospital throughout the period. Only nine patients were living independently at the time of follow-up or death, and 34 were in longer-term in-patient settings. Eighteen patients had died during the 10-year period. Clinical implications: New planning of rehabilitation services needs to ensure an integrated whole-systems approach, across in-patient and community settings, with specialist mental health rehabilitation teams to support people moving from hospital to the community, and for the small number remaining in hospital for very long periods, development of sufficient high-quality, local in-patient provision.